Spiritual health in the reform of spanish renaissance nursing. - Muñoz Devesa, Aarón; Bermejo Higuera, José Carlos; Galán González-Serna, José María; Morales Moreno, Isabel (Revista Cuidarte)
Introduction: For decades, spirituality has been rediscovered by health sciences, offering a foundation for how individuals relate to themselves, others, nature, or the transcendent. It is shaped by values and beliefs that guide salutogenic behaviors. However, theoretical development is still necessary, and the history of nursing is a place to find referents. Objective: To historically validate the concept of spiritual health through the nursing care of St. John of God, the father reformer of nursing within the Hispanic Catholic ambit. Materials and Methods: Historiographic study based on the works of St. John of God and his mentor, spiritual master, and promoter, St. John of Avila. The categories of analysis were the definition and the four domains of spiritual health following Fisher's model. Results-Discussion: Comprehensive care of the human being encompassing the four domains was observed. Self: Self-care, introspection, and balance; Others: Compassion, empathy, and humane treatment; Nature: Contact with nature for healing; Transcendence: Religious faith as a source of meaning and peace. For John of God, spiritual health is the complete fulfillment of the individual. Conclusions: Nursing practices of St. John of God validate the concept of spiritual health within Hispanic nursing. Therefore, we can affirm that his ideas may be relevant to nursing today.